2019
DOI: 10.2147/dddt.s211630
|View full text |Cite
|
Sign up to set email alerts
|

<p>A randomized controlled trial evaluating the effects of amlodipine on myocardial iron deposition in pediatric patients with thalassemia major</p>

Abstract: Background Mortality rates increase due to iron deposition in the cardiac muscles of thalassemia major (TM) patients. Iron overload cardiomyopathy could be treated with a combination therapy of an iron chelator and an L-type calcium channel blocker. We designed a randomized controlled study to assess the potential of amlodipine, alongside chelation, in reducing myocardial iron concentration in TM patients compared with a placebo. Objectives This study aims to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 39 publications
5
29
0
Order By: Relevance
“…VIT-2763 has been shown to ameliorate oxidative stress, improve erythropoiesis by reducing the aggregation of a chains hence mitigating iron overload in thalassemic mice (110). Iron chelators combined with amlodipine, an L-type calcium channel blocker, were also used in a recent randomized clinical trial in pediatric patients (90).…”
Section: Iron and Hematopoiesismentioning
confidence: 99%
“…VIT-2763 has been shown to ameliorate oxidative stress, improve erythropoiesis by reducing the aggregation of a chains hence mitigating iron overload in thalassemic mice (110). Iron chelators combined with amlodipine, an L-type calcium channel blocker, were also used in a recent randomized clinical trial in pediatric patients (90).…”
Section: Iron and Hematopoiesismentioning
confidence: 99%
“…9,10 Amlodipine as a calcium channel blocker (CCB) is accessible at an affordable price, oral administration, known safety profile, a long half-life (35 to 50 hours) and convenient drug. 11 The promising effect on the improvement of myocardial iron overload subsequent to amlodipine prescribed alongside standard iron chelators can propound it in the management of cardiac siderosis amongst iron overloaded thalassemia cases, without serious side effects. [11][12][13] A systematic review, comprising two randomised controlled trials (n = 74), reported that a significant boost was detectable in myocardial relaxation after amlodipine therapy in comparison to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…11 The promising effect on the improvement of myocardial iron overload subsequent to amlodipine prescribed alongside standard iron chelators can propound it in the management of cardiac siderosis amongst iron overloaded thalassemia cases, without serious side effects. [11][12][13] A systematic review, comprising two randomised controlled trials (n = 74), reported that a significant boost was detectable in myocardial relaxation after amlodipine therapy in comparison to the control group. However, the results remained inconclusive due to feeble available evidence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations